Pengaruh Teknologi Informasi Dan Kualitas Pelayanan Terhadap Kepuasan Nasabah - Rifanny Maulana; Iswandi Sukartaatmadja (Jurnal Informatika Kesatuan, 2022)
Economic growth in this modern age makes business competition tighter. Banking becomes one of the services industry that supports economic growth in Indonesia. The banking industry is also one of the donations of national donations and serves as an institution to accommodate the funds of the public funds, it can also be relulated in productive economic activities. Thus, the benchmark of success of a bank, one of which depends on the number of customers. The more customers are interested, the more funds are immediately and reconclab by achievement maximum profitability. The purpose of this study is (1) to know and analyze the influence of information technology on customer satisfaction, (2) to know and analyze the effect of service quality to customer satisfaction, (3) to know and analyze the influence of information technology and service quality together with customer satisfaction of the number of respondents in this study amounted to 100 respondents taken from the community of Bogor City. Research data is processed using SPSS. The results of this study are as follows: (1) Information Technology has a positive and significant effect on customer satisfaction at Bank Mandiri with the value of regression coefficient by 0.453 and has a significant value of 0.000. (2) The quality of service has a positive and significant effect on customer satisfaction at Bank Mandiri with the value of regression coefficient by 0.443 and has a significant value of 0.000. (3) Information technology and service quality has a positive and significant effect on customer satisfaction at Bank Mandiri with a value of F Count of 47,650 and larger than the F table of 2.70 and has a significance value of 0.000. Keywords: Information Technology, Quality Services and Customer Satisfaction